2015
DOI: 10.1111/bjd.13884
|View full text |Cite
|
Sign up to set email alerts
|

Risk of skin ulcerations associated with oral nicorandil therapy: a population‐based study

Abstract: Use of nicorandil was found to be associated with an increased risk for skin ulceration, especially in the first year after incident exposure. We suggest that regulatory agencies re-evaluate the risk for skin ulceration associated with use of nicorandil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
1
11
0
1
Order By: Relevance
“…reported an incidence of 0·37% for anal ulcers only , and Lee et al . recently reported a high incidence of 2·3% for skin ulcers in patients treated with nicorandil in Taiwan .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported an incidence of 0·37% for anal ulcers only , and Lee et al . recently reported a high incidence of 2·3% for skin ulcers in patients treated with nicorandil in Taiwan .…”
Section: Discussionmentioning
confidence: 99%
“…Also, because our data collection procedures were not exhaustive, we did not estimate the incidence over the period. Colvin et al reported an incidence of 0⋅37% for anal ulcers only (41), and Lee et al recently reported a high incidence of 2⋅3% for skin ulcers in patients treated with nicorandil in Taiwan (87). In France, sales of drugs containing nicorandil decreased by half between 2010 and 2015 (88,89), and a decrease in NIUs is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Depuis 2002, des localisations extra-orales des ulcérations dues au nicorandil ont été rapportées, principalement au niveau du tractus gastro-intestinal et de la zone péri-anale [22,23], de la cornée et de la conjonctive [24], de l'appareil génital [25] et de la peau [26]. Les lésions du tractus digestif peuvent être responsables d'hémorragies, fistules et perforations, complications graves, nécessitant une prise en charge urgente et adéquate.…”
Section: Discussionunclassified
“…In this issue of the BJD, Lee et al 6 examined the association between oral nicorandil use and risk of skin ulcerations, based on one million individuals assembled from a claim database. As the first population-based cohort study on this topic, this study represents an innovative approach to exploring drug safety, highlighted by the large sample size, a set of covariates, and a temporal relationship of the exposure-outcome ensured by the prospective design.…”
Section: Original Article P 498mentioning
confidence: 99%
“…Indeed the major findings of this study, including the demographic features and disease characteristics, are quite similar to those reported by other registries and/or observational studies of biologics in psoriasis. [2][3][4][5][6] Patients enrolled in BADBIR had both extensive skin involvement and a severe impairment of quality of life, as measured by the high mean Psoriasis Area and Severity Index and Dermatology Life Quality Index scores (16Á2 AE 8Á1 and 16Á2 AE 7Á4, respectively). Patients in the biologics cohort had a higher psoriasis severity and a poorer quality of life than those in the conventional cohort.…”
Section: Original Article P 510mentioning
confidence: 99%